DORIS LESSING’S “LITTLE TEMBI” AND POST-COLONIAL CRITICISM - Casagrande, Sarah; Bonnici, Thomas (Línguas & Letras, 2007)
Colonial strategies, including degradation and the othering of the colonial subject are analyzed in the short story “Little Tembi” by Doris Lessing. The manner an African boy is othered by white plantation owners and his resistance against the colonial and apartheid system through sly civility and crime are investigated.